Conclusions (Scottish Historical and Archaeological Internet Reports, 2009)
Of the range of deposits identified, what is most interesting is probably the distribution of medieval material, which confirms the previously supposed limits of the medieval core. The other main achievement of the work is the identification of certainly one, and possibly two sections of wall which may be the elusive town wall. The new evidence will inform planning decisions within the burgh and methodologies for future work.